Effectiveness of the new mandatory mouthguard use and orodental injuries in Dutch field hockey - Cicek, T.; Dhamo, B.; Wolvius, E. B.; Wesselink, P. R.; Kragt, L. (The Physician and Sportsmedicine, 2021)
Objectives Up to 68% of field hockey players have experienced at least one orodental injury in their sport career. Therefore, the Royal Dutch Hockey Association (KNHB) made mouthguard use mandatory for field hockey players during competition and training from August 2015 onwards. This study evaluates the effects of the new regulations on mouthguard use and the occurrence of injuries in Dutch field hockey.